Feresa Gray 1870 - James G. Mead; Robert L. Brownell, Jr. (Smithsonian Institution Press, 1993)
Feresa Gray, 1870. Proc. Zool. Soc. Lond., 1870(1):77. TYPE SPECIES: Delphinus intermedius Gray, 1827 (= Feresa attenuata Gray, 1875). COMMENTS: Delphinus intermedius Gray, 1827 was preoccupied by Delphinus intermedius Harlan, 1827 (= Globicephala mêlas). Gray subsequentally changed generic designations of that nominal taxon ( Grampus intermedius Gray, 1843; Orca intermedia Gray, 1846). Published as part of James G. Mead & Robert L. Brownell, Jr., 1993, Order Cetacea, pp. 349-364 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 352, DOI: 10.5281/zenodo.7352970